Effects of external counterpulsation on postexercise recovery in elite rugby league players - Roberts, L. A.; Caia, J.; James, L. P.; Scott, T. J.; Kelly, V. G. (International Journal of Sports Physiology and Performance, 2019)
Purpose: External counterpulsation (ECP) has previously been used to treat cardiac patients via compression of the lower extremities during diastole to increase venous return and coronary perfusion. However, the effects of ECP on exercise performance and markers of recovery in elite athletes are largely unknown. Methods: On 2 separate occasions, 48 h apart, 7 elite National Rugby League players performed an identical 60-min field-based conditioning session followed by a 30-min period of either regular ECP treatment or placebo. Power measures during repeated cycle bouts and countermovement jump height and contraction time derivatives were measured at rest and 5 h postexercise. Saliva samples and venous blood samples were taken at rest, postexercise, and 5 h postexercise to assess stress, inflammation, and muscle damage. Results: After ECP treatment, cycling peak power output (P=.028; 11%) and accumulated peak power (P=.027; 14%) increased compared with the placebo condition. Postexercise plasma interleukin 1 receptor antagonist only increased after ECP (P=.024; 84%), and concentrations of plasma interleukin 1 receptor antagonist tended to be higher (P=.093; 76%) 5 h postexercise. Furthermore, testosterone-to-cortisol ratio was increased above baseline and placebo 5 h postexercise (P=.017-.029; 24-77%). The ratio of postexercise salivary Alpha-amylase to immunoglobulin A decreased after treatment (P=.013; 50%) compared with the placebo control. Conclusions: Exercise performance and hormonal indicators of stress were improved and inflammation markers were reduced following acute ECP.